Professorial lecture: "personalized therapy - the perspectives of pharmaceutical technology" / Zakiah Mohd Noordin and Dr. Gurmeet Kaur Surindar Singh - Mohd Noordin, Zakiah; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2023)
Professor Dr Wong Tin Wui, popularly known as Prof Wong, is a Professor of Pharmaceutical Technology at the Department of Pharmaceutics, Faculty of Pharmacy, Universiti Teknologi MARA (UiTM), Puncak Alam. He is also at present the Principal Fellow at Non-Destructive Biomedical and Pharmaceutical Research Centre, Smart Manufacturing Research Institute, UiTM Puncak Alam. Prof Wong has written more than 120 research papers in peer reviewed journals, mainly in the area of nano drug delivery sciences, focusing on oral, pulmonary and skin medicine for cancer, diabetes and infection treatment.